2004
DOI: 10.4049/jimmunol.173.12.7435
|View full text |Cite
|
Sign up to set email alerts
|

Innate Imprinting by the Modified Heat-Labile Toxin of Escherichia coli (LTK63) Provides Generic Protection against Lung Infectious Disease

Abstract: In a healthy individual, the lung contains few lymphoid cells. However, amplified immune responses, as exemplified during lung infection, can cause extensive tissue damage. We have previously demonstrated that one lung infection modulates the immunopathological outcome to a subsequent unrelated pathogen. Mimicking heterologous immunity may provide a means of enhancing both innate and acquired immunity. We now show that prior lung administration of a modified heat-labile toxin from Escherichia coli (LTK63) enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 48 publications
4
57
0
2
Order By: Relevance
“…In agreement with a previous report and with the data originated from the BAL, we found that LTK63 administration triggered the recruitment at 6 -8 days of CD4 ϩ T cells, CD8 ϩ T cells, NK cells (Fig. 5, A-C), and B cells (data not shown) (21). We extended the analysis of lung single cell suspension by monitoring the activation status of T and NK cells.…”
Section: Ltk63 Activates Cd4 ϩ and Cd8 ϩ T Cells In The Lungsupporting
confidence: 77%
See 2 more Smart Citations
“…In agreement with a previous report and with the data originated from the BAL, we found that LTK63 administration triggered the recruitment at 6 -8 days of CD4 ϩ T cells, CD8 ϩ T cells, NK cells (Fig. 5, A-C), and B cells (data not shown) (21). We extended the analysis of lung single cell suspension by monitoring the activation status of T and NK cells.…”
Section: Ltk63 Activates Cd4 ϩ and Cd8 ϩ T Cells In The Lungsupporting
confidence: 77%
“…It has been shown that the pulmonary administration of LTK63 affects the composition of lung cellularity, indicating a recruitment of several blood cell types (21). The B cell and T cell gene clusters identified by hierarchical clustering analysis (Fig.…”
Section: Chemokine and Cell Signature Gene Expression Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar approach, activation of TLR2/6 and TLR9 by pre-treatment with synthetic agonists reduced parainfluenza virus titres in guinea pigs; however, this regimen was not able to prevent virus-induced airway hyperreactivity (Drake et al, 2013). Similar to the immunostimulatory effect of individual TLR agonists, innate immune imprinting by local application of modified heat-labile Escherichia coli toxins has been shown to confer protection against respiratory viral infection in murine models (Norton et al, 2010;Williams et al, 2004). The need for local application might even be circumvented by dietary intake of probiotics, specifically those bacterial strains that trigger type I IFN production by plasmacytoid DCs (Jounai et al, 2015).…”
Section: Direct Interactions Of Bacteria and Viruses: Altered Virulenmentioning
confidence: 96%
“…A cárie é uma doença oral de caráter crônico e infeccioso, definida pela Organização Mundial de Saúde (OMS) como um dos principais problemas de saúde pública no mundo (PETERSEN, 2003;WORSLEY et al, 2016). Essa doença atinge países subdesenvolvidos ou mesmo aqueles mais desenvolvidos, sendo as populações mais desfavorecidas as mais afetadas.…”
Section: A Cárie Dental E O Streptococcus Mutansunclassified